Digital terrain mapping by the OSIRIS-REx mission. (January 2020) - Barnouin, O.S.; Daly, M.G.; Palmer, E.E.; Johnson, C.L.; Gaskell, R.W.; Al Asad, M.; Bierhaus, E.B.; Craft, K.L.; Ernst, C.M.; Espiritu, R.C.; Nair, H.; Neumann, G.A.; et al.
Abstract: The Origins, Spectral Interpretation, Resource Identification, Security–Regolith Explorer mission will return a sample to Earth from asteroid (101955) Bennu. Digital terrain models (DTMs) of the asteroid, and products enabled by them, are key to understanding the origin and evolution of the asteroid, providing geological and geophysical context for the sample, maximizing the amount of sample returned, navigating the spacecraft, and ensuring the safety of the spacecraft during sampling. The mission has two approaches for producing these DTMs: a camera-based approach and a lidar-based approach. We provide an overview of the methods used for these two approaches and how they fit into the originally planned mission. We also discuss a summary of tests using these plans to evaluate the expected performance of the DTMs and describe the data products derived from them. Highlights: OSIRIS-REx uses two approaches to make digital terrain maps of asteroid Bennu. Digital terrain maps are produced at global and local scales. Global shape models from images and laser altimetry achieve 1 to 0.1 m accuracy. A simulated truth shape model shows that stereophotoclinometry is effective. Products such as geopotential elevation, slope, and tilt can be derived from the DTMs.